2008
DOI: 10.1016/j.molcel.2008.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Methylation of FOXO Transcription Factors Inhibits Their Phosphorylation by Akt

Abstract: Forkhead box O (FOXO) transcription factors, the key regulators of cell survival, are negatively controlled through the PI3K-Akt signaling pathway. Phosphorylation of FOXO by Akt leads to cytoplasmic localization and subsequent degradation via the ubiquitin-proteasome system. Here we show a paradigm of FOXO1 regulation by the protein arginine methyltransferase PRMT1. PRMT1 methylated FOXO1 at conserved Arg248 and Arg250 within a consensus motif for Akt phosphorylation; this methylation directly blocked Akt-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
352
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(368 citation statements)
references
References 39 publications
12
352
2
2
Order By: Relevance
“…This sort of multilevel control of FOXO3 function has been demonstrated for arginine methylation and Akt phosphorylation of FOXO1 where Akt phosphorylation is the final determinant of cytosolic translocation but arginine methylation of FOXO1 controls access of Akt to it substrate serine site. 16 It is notable that our studies show that aspartic acid substitution of S-574 alone is sufficient to induce apoptosis, suggesting that once that residue becomes charged, changing acetylation state may not be critical. The exact identity of the gene expression changes responsible for FOXO3-dependent apoptosis has been a matter of debate.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This sort of multilevel control of FOXO3 function has been demonstrated for arginine methylation and Akt phosphorylation of FOXO1 where Akt phosphorylation is the final determinant of cytosolic translocation but arginine methylation of FOXO1 controls access of Akt to it substrate serine site. 16 It is notable that our studies show that aspartic acid substitution of S-574 alone is sufficient to induce apoptosis, suggesting that once that residue becomes charged, changing acetylation state may not be critical. The exact identity of the gene expression changes responsible for FOXO3-dependent apoptosis has been a matter of debate.…”
Section: Discussionmentioning
confidence: 72%
“…Specific PTMs regulate the partitioning of FOXO3 between the cytosol and the nucleus [8][9][10][11][12][13][14][15] and its stability and degradation, 16 but the links between specific PTMs and FOXO3 transcriptional specificity are less well understood.…”
mentioning
confidence: 99%
“…Recent studies from our laboratory have shown that the combination of HCV and alcohol specifically suppresses arginine methylation of FOXO3, 47 and this is expected to make it a better substrate for Akt phosphorylation, causing nuclear export and degradation. 48 Because the effects can be seen in our transgenic mice and infected cells, the HCV structural proteins, particularly core, may play a critical role in FOXO3 modulation. This would not be unexpected because the core protein itself has been implicated as a major cause of HCV-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…As a transcription factor, FOXO3 regulates expression of several target genes that participate in a series of cellular processes and respond to various cellular stresses (4)(5)(6)(7)(8). Alternatively, different cellular stresses cause variant statuses of posttranslational modifications of FOXO3, such as phosphorylation, ubiquitination, acetylation, and methylation, which in turn regulate the stability or activity of FOXO3 (9)(10)(11)(12)(13)(14).…”
Section: F Orkhead Box O (Foxo) Transcription Factors Homologsmentioning
confidence: 99%